“Being quadrilheiro”: subjectivity and affective culture within the square dance of june competitives in the Ceará/Brazil - Silva de Castro, Thiago (Revista de Ciências Sociais, 2023)
The discussions developed in this paper are the result of an ongoing research on feast of Saint John with square dance in the state of Ceara/Brazil. The so-called ‘June fest' establishes a symbolic space permeated by feelings, ranging from rivalry, to belonging, to what many classify as ‘love for square dance’. In this context, a mosaic of emotions appears as fuel for this universe, mixing with practices and conceptions that help to institute a kind of ‘identity ideal’, which here I call ‘being a quadrilheiro’. Taking this aspect into account, this work takes a look at the June fest focusing on the feelings raised, as well as the meanings mobilized in the social processes experienced by the individuals who produce this manifestation.